CONCEPT OF AN AI-BASED ADAPTIVE MODEL FOR TEACHING ENGLISH IN MILITARY CONTEXTS THROUGH ARTIFICIAL INTELLIGENCE (AI) AND NATURAL LANGUAGE PROCESSING (NLP) TECHNOLOGIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the conceptual foundations and practical implementation of an AI-based adaptive learning model for teaching English to cadets, supported by NLP technologies. It emphasizes the scientific, pedagogical, and technological rationale for this model and argues for its necessity in transforming language training in military institutions.